Minimally Invasive Treatment of Recurrent Anal Fistulas with Autologous Platelet-Rich Plasma Combined With Internal Orifice Closure. (February 2023) - Cwaliński, Jarosław; Hermann, Jacek; Paszkowski, Jacek; Banasiewicz, Tomasz
Aim: Minimally invasive procedures for the treatment of anal fistulas are gaining more and more popularity. For this purpose, Platelet-Rich Plasma (PRP) are administered to accelerate the healing process of various difficult wounds or lesions. The aim of this study was to evaluate preliminary results of PRP injection into the tissues adjacent to anal fistulas. Patients and methods: A cohort of 42 patients with recurrent anal fistula, who underwent at least one cutting procedure previously, were enrolled into this preliminary and prospective trial. Closure of internal orifice was performed in all investigated patients, however, in 22 patients from group I, that procedure was combined with topical injection of PRP. In the postoperative period, the PRP administration could be repeated in case of incomplete fistula closure. Follow-up consisted of out-patient visits in a fortnight, 1, 2, and 12 months. Results: Complete closure of anal fistulas was achieved in 16 (75%) patients from group I and 10 (45, 5%) patients from group II. The fistulas were healed in 9 patients from group I after single application of PRP. In the next 9 patients with incomplete fistula closure, the injection was repeated 2 to 4 times every fortnight leading finally to complete recovery in 6 of them. Conclusions: Surgical fistula closure with local PRP application spares the anal sphincter and gives the opportunity to repeat the procedure several times if necessary. Treatment of recurrent anal fistulas with PRP can be considered as last resort therapy.